Anionic redox in Na-based layered oxide cathodes: a review with focus on mechanism studies. (September 2020) - Li, C.; Geng, F.; Hu, B.; Hu, B.
Abstract: Among the potential cathode candidates for Na-ion batteries (NIBs), Na-based layered transition-metal oxides hold the greatest promise by virtue of their appropriate energy density, environmental benignity, and affordable synthesis. However, the theoretical energy density of most layered oxide cathodes is limited as their charge compensation process relies solely on the cationic redox of transition-metal (TM) ions. To break this shackle, anionic redox has emerged as a lever to improve the energy density of layered oxides. Herein, a systematic overview of the latest progresses on anionic-redox-active layered oxide cathodes is presented, with focus on the mechanism studies of anionic redox reaction. The practical challenges of anion redox in layered oxides are also summarized, and the possible solutions are suggested. In contrast to the Li-ion system, anion redox activity is uncovered for both Na-rich and Na-deficient layered oxides, and their underlying anionic reaction mechanisms exhibit many discrepancies. Moreover, the promise of utilizing sole anionic redox in NIBs with earth-abundant and low-cost elements is also considerable. This overview could provide robust guidance for further development of high-energy layered oxide cathodes with anionic redox activity. Graphical abstract: A systematic overview of the latest progresses on anionic redox in Na-based layered oxide cathodes is presented, with focus on the mechanism studies. The practical challenges of anion redox in Na-based layered oxides are also summarized, and the possible solutions are suggested. The related anionic reaction mechanisms exhibit many differences from the Li-ion system. Image 1 Highlights: A systematic review on anionic redox in Na-based layered oxide cathodes is presented. The practical challenges of anion redox in Na-based layered oxides are summarized. The anionic reaction mechanisms exhibit many differences from the Li-ion system.